2011
DOI: 10.1111/j.1365-2699.2011.02491.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic beta diversity reveals historical effects in the assemblage of the tree floras of the Ryukyu Archipelago

Abstract: Quantifying the roles of historical versus contemporary constraints in determining species diversity is a central issue in island biogeography, and the phylogenetic beta diversity between islands is an essential measure specifying the influence of historical barriers on insular assemblages. In this study, using phylogenetic information for 513 tree species on 26 islands in the subtropical Ryukyu Archipelago, phylogenetic beta diversity between islands was calculated, and effects of historical factors (gaps as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
(31 reference statements)
5
26
0
Order By: Relevance
“…Our study adds to the growing body of literature exploring community assembly processes across the biodiverse Ryūkyū archipelago (e.g. Hirao et al, 2015;Kubota, Hirao, Fujii, & Murakami, 2011;Wepfer et al, 2016), and we demonstrate for the first time how extensions of island biogeography theory might apply to the Ryūkyū archipelago. Previous work in this system has suggested that both current and historic environmental factors should be considered simultaneously when assessing diversity of the Ryūkyūs (Nakamura, Suwa, Denda, & Yokota, 2009) and that climate and historic land connectivity drives ant community composition across the islands of East Asia (Wepfer et al, 2016).…”
Section: Context and Future Directionsmentioning
confidence: 64%
“…Our study adds to the growing body of literature exploring community assembly processes across the biodiverse Ryūkyū archipelago (e.g. Hirao et al, 2015;Kubota, Hirao, Fujii, & Murakami, 2011;Wepfer et al, 2016), and we demonstrate for the first time how extensions of island biogeography theory might apply to the Ryūkyū archipelago. Previous work in this system has suggested that both current and historic environmental factors should be considered simultaneously when assessing diversity of the Ryūkyūs (Nakamura, Suwa, Denda, & Yokota, 2009) and that climate and historic land connectivity drives ant community composition across the islands of East Asia (Wepfer et al, 2016).…”
Section: Context and Future Directionsmentioning
confidence: 64%
“…Continental island archipelagos are formed by the interplay of tectonic, geographical, and palaeoclimatic processes (Whittaker and Fernández-Palacios 2007). Their biotas have been repeatedly fragmented because sea level changes that produced discrete colonisation windows when land bridges formed (Kubota et al 2011); this allowed continental islands to function as evolutionary cradles for neo-endemics or refugia for relict taxa that escaped harsh continental climates during the Quaternary ice age (Tiffney 1985, Harrison et al 2001. Although oceanic islands have been regarded as natural laboratories of adaptive radiation through niche pre-emption by the lineages that first colonise the islands (Whittaker et al 2008, Weigelt andKreft 2013), continental islands are suitable for testing the roles of idiosyncratic historical processes, such as nonadaptive radiations associated with divergent selection or Islands and fragmented habitats serve as ideal systems for studying ecological and evolutionary processes; thus, biodiversity patterns relevant to geographical constraints have long been a central issue in ecology and conservation biology (Whittaker and Fernández-Palacios 2007).…”
mentioning
confidence: 99%
“…Phylogenetic (DNA-based) dissimilarity measures, such as UniFrac (Lozupone & Knight, 2005), may also be used as an alternative measurement of island dissimilarity. As environmental survival and dispersal ability are also phylogenetically determined (Pearman et al, 2008), phylogenetic dissimilarity may reveal the historical constraints of environmental differences across a system, if there is a strong ecological gradient (Kubota et al, 2011).…”
Section: Dissimilarity Measuresmentioning
confidence: 99%
“…In an application of this concept, phylogenetic dissimilarity (Sanmart ın et al, 2008) has been utilized to provide insight into the historical constraints of the distributions of species between islands in the Japanese Ryukyu Islands (Kubota et al, 2011). Identifying and quantifying the dispersal barriers (also referred to as "geohistorical" barriers; Kubota et al, 2011) and/or ecological constraints (i.e. "habitat filtering"; Cornwell et al, 2006), which have acted on plant dispersal and development, are important factors for understanding area plant assemblages (Thornton et al, 2002;Silvertown, 2004;Kadmon & Allouche, 2007;Kubota et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation